Imagina ebook - Herrera, Juan Felipe (2020)
A buoyant, breathtaking poem from Juan Felipe Herrera — brilliantly illustrated by Caldecott Honoree Lauren Castillo — speaks to every dreaming heart. Now in a Spanish-language edition! ¿ALGUNA VEZ has imaginado quién serás cuando crezcas? Cuando Juan Felipe Herrera era niño, recogió flores, ayudó a su mamá a alimentar a los pollitos, durmió bajo el cielo centelleante y aprendió a decirles adiós a sus amiguitos cada vez que su familia seguía el camino campesino. Al crecer, Juan Felipe Herrera se convirtió en poeta. Su hermoso poema, "Imagina" y las sugerentes ilustraciones de Lauren Castillo le hablarán a cada lector y soñador que está buscando su lugar en la vida. ¿Quién podrías llegar a ser? Imagina . . . Have you ever imagined what you might be when you grow up? When he was very young, Juan Felipe Herrera picked chamomile flowers in windy fields and let tadpoles swim across his hands in a creek. He slept outside and learned to say goodbye to his amiguitos each time his family moved to a new town. He went to school and taught himself to read and write English and filled paper pads with rivers of ink as he walked down the street after school. And when he grew up, he became the United States Poet Laureate and read his poems aloud on the steps of the Library of Congress. If he could do all of that . . . what could you do? With this newly translated illustrated poem of endless possibility, Juan Felipe Herrera and Lauren Castillo breathe magic into the hopes and dreams of readers searching for their place in life.